Low-temperature activated carbon, preparation method and application thereof

By adopting low-temperature activation technology in the preparation of activated carbon, utilizing the reaction of the polymer precursor and benzoyl peroxide, combined with a nitrogen atmosphere and appropriate activators, the activation temperature was successfully reduced and the energy consumption and corrosion problems caused by high-temperature activation were solved. , to prepare activated carbon products with larger specific surface area and more developed pore structure.

CN116375031BActive Publication Date: 2025-01-21XIAN XD POWER CAPACITOR CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310411232.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-17
Publication Date
2025-01-21
Estimated Expiration
2043-04-17

AI Technical Summary

Technical Problem

In the prior art, the activation process of activated carbon requires high temperature, resulting in large energy consumption and serious corrosion of the activator on the equipment, affecting production efficiency and safety.

Method used

A low-temperature activated activated carbon preparation method is adopted, by reacting the polymer precursor with benzoyl peroxide in hydrochloric acid, then adding cetyldimethylethylammonium bromide, and pre-carbonizing and calcining it under a nitrogen atmosphere , use activators such as carbamoyl phosphate disodium salt to lower the activation temperature.

Benefits of technology

It realizes the preparation of low-temperature activated activated carbon, reduces energy consumption, reduces the risk of corrosion of equipment by the activator, increases the specific surface area and pore structure of the product, and is suitable for water treatment, chemical catalysts and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116375031B_ABST
    Figure CN116375031B_ABST
Patent Text Reader

Abstract

The present invention provides a kind of low-temperature activated activated carbon, preparation method and application, which belong to the field of activated carbon nanomaterials. The raw materials used are common and easily available industrial-grade products, the equipment is simple, the preparation process is simple, the repeatability is strong, and it is conducive to industrial large-scale production. The present invention provides a kind of low-temperature activated activated carbon, the activation temperature is relatively low, and the corrosion of the activator to the equipment is relatively small, which not only further reduces the cost of the product, but also is human and environmentally friendly, and can be widely used in water treatment, chemical catalysts and carriers, solvent recovery, oil decolorization, air purification and other fields. Compared with the existing commercially available activated carbon, the product prepared by the present invention has a large specific surface area, a more developed pore structure, and a lower iron content in the product. In addition, the product of the present invention can be used in the fields of heavy metal ion adsorption in aqueous solution, automobile exhaust purification, impurity removal of printing ink, gas separation, supercapacitor electrode materials and other electrochemical energy storage materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of activated carbon nanomaterials, in particular to low-temperature activated activated carbon, a preparation method and application thereof. Background Art

[0002] Activated carbon is a black porous solid material, mainly composed of carbon, and contains a small amount of oxygen, hydrogen, sulfur, nitrogen, chlorine and other elements. Due to its rich pore structure and huge specific surface area, and no toxic side effects and secondary pollution, it is currently recognized as a highly efficient adsorption material in the world. It can effectively adsorb harmful gases and odors. In the treatment of indoor pollution, activated carbon is also considered to be the most environmentally friendly treatment product. In addition, activated carbon also has the characteristics of catalysis, flexibility, wear resistance, and conductivity. It is widely used in water treatment, chemical catalysts and carriers, gas purification, solvent recovery, oil decolorization, gold extraction, tail liquid recovery, automobile exhaust purification, impurity removal of printing inks, gas separation, electrochemical energy storage materials and other fields.

[0003] For example, Chinese invention patent CN202110058052.4 uses the continuous rigid biphenyl structure in the triazine-based cross-linked microporous polymer molecular chain as the carbon source and the triazine ring structure as the nitrogen source. Through high-temperature carbonization and potassium hydroxide pore activation, a microporous polymer-derived nitrogen-rich porous activated carbon adsorbent is prepared. 2+ Heavy metal ions such as straw have excellent pore adsorption characteristics. Chinese patent CN202110846095.9 discloses a method for preparing activated carbon using straw as raw material. The method uses zinc oxide as an activator. First, the straw particles and zinc oxide are heated to react in a nitrogen atmosphere, and then phosphoric acid is added. Activated carbon with good adsorption properties is prepared by high-temperature carbonization and hydrochloric acid post-treatment. Chinese invention patent CN201510868434.8 provides a method for preparing activated carbon by KOH solid activation. The method first grinds the KOH solid into powder, then adds an activated carbon precursor, and calcines and carbonizes it at a high temperature of 700-1000°C in a nitrogen atmosphere, and finally washes and dries it. Although the activated carbon prepared by the above patent is of good quality, the use of zinc oxide or KOH as an activator makes the reaction temperature high, the reaction process consumes a lot of energy, and KOH corrodes the equipment severely. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a low-temperature activated carbon, a preparation method and an application thereof.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing low-temperature activated carbon comprises the following steps:

[0007] 1) adding a polymer precursor and benzoyl peroxide in a molar ratio of 1:(0.1-0.6) to 3.5% hydrochloric acid, and then adding hexadecyl dimethyl ethyl ammonium bromide to obtain a reaction solution, reacting the reaction solution at 0-3° C. for 4-12 hours, and after the reaction is completed, collecting the solid product for washing and drying;

[0008] 2) pre-carbonizing the dried product under a nitrogen atmosphere at a temperature of 380-480° C. for 1-1.5 hours, and then grinding the product;

[0009] 3) The product and the activator are uniformly mixed in a mass ratio of 1:(0.8-1.8), and calcined in a nitrogen atmosphere at a calcination temperature of 380-550° C. for 1.5-2 hours. After the calcination, the collected solid product is sequentially acid-washed and water-washed, and then dried to obtain an activated carbon product.

[0010] Furthermore, the polymer precursor in step (1) is vinyl pyrrolidone, pyrrole, methyl acrylate, ethyl acrylate, 2-methyl methacrylate, 2-ethyl methacrylate, acrylamide, methacrylamide, dimethylaminopropyl acrylamide, aniline, p-chloroaniline, 2-fluoroaniline, 4-fluoroaniline, methylaniline or 2-ethylaniline.

[0011] Furthermore, in step (1), the concentration of benzoyl peroxide in the reaction solution is 0.1 to 0.5 mol / L.

[0012] Furthermore, the concentration of hexadecyl dimethyl ethyl ammonium bromide is 0.01 to 0.1 mol / L.

[0013] Furthermore, in step (3), the activator is disodium carbamoyl phosphate, sodium aminosulfonate, sodium aminobenzenesulfonate, sodium diformylamide or potassium aminosulfonate.

[0014] A low-temperature activated carbon is prepared according to the above method.

[0015] Furthermore, it is in the shape of a nano ring.

[0016] Furthermore, a large number of micropores and mesopores are distributed in the low-temperature activated carbon.

[0017] Furthermore, it can be used as an adsorbent material for heavy metal ion adsorption in aqueous solution, automobile exhaust purification, impurity removal of printing ink and gas separation; or / and

[0018] As supercapacitor electrode material or energy storage material.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The invention provides a low-temperature activated carbon, a preparation method and an application thereof. The raw materials used are common and easily available industrial-grade products, the equipment is simple, the preparation process is simple, the repeatability is strong, and it is conducive to industrial large-scale production.

[0021] The present invention provides a low-temperature activated activated carbon, the activation temperature is relatively low, the activating agent has relatively little corrosion on the equipment, which not only further reduces the cost of the product, but also is friendly to the human body and the environment, and can be widely used in water treatment, chemical catalysts and carriers, solvent recovery, oil decolorization, air purification and other fields. Compared with the existing commercially available activated carbon, the present invention also has the following beneficial effects: the product has a large specific surface area, a more developed pore structure, and a lower iron content in the product. In addition, the product prepared by the present invention has distinct morphological characteristics and is in the shape of a ring. The diameter of the ring is about 200nm, and the diameter of a single product is about 50nm. The overall product has a relatively obvious pore structure, and can also be used in the fields of heavy metal ion adsorption in aqueous solution, automobile exhaust purification, impurity removal of printing ink, gas separation, supercapacitor electrode materials and other electrochemical energy storage materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a scanning electron microscope image of an activated carbon in Example 1;

[0023] Figure 2 This is a transmission electron microscope image of an activated carbon in Example 1;

[0024] Figure 3 This is an XRD diagram of an activated carbon in Example 1;

[0025] Figure 4 This is an activated carbon nitrogen isothermal adsorption-desorption curve of Example 1;

[0026] Figure 5 The product prepared by the present invention is used for performance testing of supercapacitors;

[0027] Table 1 is a comparison between the activated carbon product prepared by the present invention and the commercially available product;

[0028] Table 2 shows the effects of the products prepared by the present invention on Cu in aqueous solution 2+ Adsorption test. DETAILED DESCRIPTION

[0029] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0030] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0031] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0032] Example 1

[0033] Methyl acrylate and benzoyl peroxide were added to 100mL hydrochloric acid with a mass fraction of 3.5% in a molar ratio of 1:0.6, and the concentration of benzoyl peroxide in the mixed solution was 0.5mol / L. Then hexadecyl dimethyl ethyl ammonium bromide was added at a concentration of 0.1mol / L, and stirred to react for 12 hours at normal pressure and 3°C. After the reaction, the collected solid product was washed with deionized water for 3 times and dried at 80°C. The dried product was pre-carbonized in a nitrogen atmosphere at a temperature of 480°C for 1.5 hours, and then the product was ground for 1.5 hours; the above product was uniformly mixed with disodium carbamoyl phosphate in a mass ratio of 1:1.8, and calcined in a nitrogen atmosphere at a temperature of 550°C for 2 hours. After the calcination, the collected solid product was washed with dilute hydrochloric acid and deionized water for 3 times, respectively, and dried to obtain an activated carbon product.

[0034] See also Figure 1 , Figure 1 This is a scanning electron microscope image of an activated carbon prepared in Example 1. The product has distinct morphological characteristics and is in a circular shape with a diameter of approximately 200 nm. The diameter of a single product is approximately 50 nm, and the overall product has a relatively obvious pore structure.

[0035] See also Figure 2 , Figure 2 This is a transmission electron microscope image of the product of Example 1, which shows that the product is a typical amorphous carbon material.

[0036] See also Figure 3 , Figure 3 This is the XRD diagram of the product of Example 1. From the XRD diagram, it can be determined that the main component of the product is carbon material.

[0037] See also Figure 4 , Figure 4 This is the nitrogen isothermal adsorption-desorption curve of the product of Example 1. The curve is a typical type I curve. At a relatively low relative pressure, the nitrogen adsorption amount increases sharply, indicating that there are a large number of micropores in the product. The product curve is convex, indicating that there are a certain amount of mesopores in the product.

[0038] See also Figure 5 , Figure 5 The electrochemical performance test diagram of the product of Example 1. The prepared product was used as a supercapacitor working electrode, a platinum sheet was used as a counter electrode, mercury / mercuric oxide was used as a reference electrode, and a 6M KOH solution was used as an electrolyte to perform a constant current charge and discharge test. Figure 5 a shows that the product has a discharge capacity of up to 470F / g at 1.0A / g. Figure 5 b shows that the capacity retention rate of the product can reach 81% after 10,000 constant current charge and discharge cycles at 10A / g.

[0039] See Table 1, which shows a comparison between the product prepared by the present invention and a commercially available product. Through the comparison, it is found that the product prepared by the present invention has a larger specific surface area, a more developed pore structure, and a lower iron content than the commercially available product.

[0040] Table 1 Comparison of products prepared by the present invention and commercially available products

[0041]

[0042] See Table 2, which shows the effects of the products prepared by the present invention on Cu in aqueous solution. 2+ First, prepare 100 mg / L Cu with deionized water and copper nitrate. 2+ The standard solution was added with 150 mg of the product prepared by the present invention, stirred evenly and adsorbed for 4 h, and the Cu was detected by UV-visible spectrophotometer. 2+ concentration, and calculate the product's effect on Cu 2+ The adsorption rate.

[0043] Table 2 The products prepared by the present invention have good Cu 2+ Adsorption test

[0044]

[0045] Example 2

[0046] Ethyl acrylate and benzoyl peroxide were added to 60mL hydrochloric acid with a mass fraction of 3.5% in a molar ratio of 1:0.1, and the concentration of benzoyl peroxide in the mixed solution was 0.1mol / L. Then hexadecyl dimethyl ethyl ammonium bromide was added at a concentration of 0.01mol / L, and stirred to react for 4 hours at normal pressure of 0°C. After the reaction, the collected solid product was washed with deionized water for 3 times and dried at 80°C. The dried product was pre-carbonized in a nitrogen atmosphere at a temperature of 380°C for 1 hour, and then the product was ground for 1 hour; the above product was uniformly mixed with sodium aminosulfonate in a mass ratio of 1:0.8, and calcined in a nitrogen atmosphere at a temperature of 380°C for 1.5 hours. After the calcination, the collected solid product was washed with dilute hydrochloric acid and deionized water for 3 times, respectively, and dried to obtain an activated carbon product.

[0047] Example 3

[0048] Methacrylamide and benzoyl peroxide were added to 90mL hydrochloric acid with a mass fraction of 3.5% in a molar ratio of 1:0.5, and the concentration of benzoyl peroxide in the mixed solution was 0.4mol / L. Then hexadecyl dimethyl ethyl ammonium bromide was added at a concentration of 0.09mol / L, and stirred to react for 11 hours at normal pressure and 2°C. After the reaction, the collected solid product was washed with deionized water for 3 times and dried at 80°C. The dried product was pre-carbonized in a nitrogen atmosphere at a temperature of 480°C for 1.5 hours, and then the product was ground for 1 hour; the above product was uniformly mixed with sodium aminobenzenesulfonate in a mass ratio of 1:1.8, and calcined in a nitrogen atmosphere at a temperature of 500°C for 2 hours. After the calcination, the collected solid product was washed with dilute hydrochloric acid and deionized water for 3 times, respectively, and dried to obtain an activated carbon product.

[0049] Example 4

[0050] Dimethylaminopropyl acrylamide and benzoyl peroxide were added to 80mL hydrochloric acid with a mass fraction of 3.5% in a molar ratio of 1:0.4, and the concentration of benzoyl peroxide in the mixed solution was 0.4mol / L. Then hexadecyl dimethyl ethyl ammonium bromide was added at a concentration of 0.08mol / L, and stirred to react for 10 hours at normal pressure and 3°C. After the reaction, the collected solid product was washed with deionized water for 3 times and dried at 80°C. The dried product was pre-carbonized in a nitrogen atmosphere at a temperature of 480°C for 1.5 hours, and then the product was ground for 1 hour; the above product was uniformly mixed with potassium aminosulfonate in a mass ratio of 1:1.8, and calcined in a nitrogen atmosphere at a temperature of 550°C for 2 hours. After the calcination, the collected solid product was washed with dilute hydrochloric acid and deionized water for 3 times, respectively, and dried to obtain an activated carbon product.

[0051] Methyl acrylate, ethyl acrylate, methacrylamide and dimethylaminopropyl acrylamide in Examples 1 to 4 can be replaced by vinyl pyrrolidone, pyrrole, 2-methyl methacrylate, 2-ethyl methacrylate, acrylamide, aniline, p-chloroaniline, 2-fluoroaniline, 4-fluoroaniline, methylaniline and 2-ethylaniline.

[0052] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing low-temperature activated carbon, characterized in that: The following steps are involved: 1) Add the polymer precursor and benzoyl peroxide in a molar ratio of 1:(0.1-0.6) to 3.5% hydrochloric acid, and then add hexadecyl dimethyl ethyl ammonium bromide to obtain a reaction solution, react the reaction solution at 0-3°C for 4-12 hours, and after the reaction is completed, collect the solid product for washing and drying; 2) The dried product is pre-carbonized in a nitrogen atmosphere at a temperature of 380-480°C for 1-1.5 hours, and then the product is ground; 3) The product and the activator are uniformly mixed in a mass ratio of 1: (0.8-1.8), and calcined in a nitrogen atmosphere at a calcination temperature of 380-550° C. for 1.5-2 hours. After the calcination, the collected solid product is acid-washed and water-washed in sequence, and then dried to obtain an activated carbon product; Wherein, the polymer precursor in step (1) is vinyl pyrrolidone, pyrrole, methyl acrylate, ethyl acrylate, 2-methyl methacrylate, 2-ethyl methacrylate, acrylamide, methacrylamide, dimethylaminopropyl acrylamide, aniline, p-chloroaniline, 2-fluoroaniline, 4-fluoroaniline, methylaniline or 2-ethylaniline; The activator in step (3) is disodium carbamoyl phosphate, sodium aminosulfonate, sodium aminobenzenesulfonate, sodium diformylamide or potassium aminosulfonate; The low-temperature activated carbon is in the shape of a nano-ring, with micropores and mesopores distributed inside.

2. The method for preparing low-temperature activated carbon according to claim 1, characterized in that: The concentration of benzoyl peroxide in the reaction solution in step (1) is 0.1-0.5 mol / L.

3. The method for preparing low-temperature activated carbon according to claim 1, characterized in that: The concentration of hexadecyl dimethyl ethyl ammonium bromide is 0.01~0.1 mol / L.

4. A low temperature activated activated carbon, characterized in that: Prepared according to the method according to any one of claims 1 to 3.

5. The use of low-temperature activated carbon according to claim 4, characterized in that: It can be used as an adsorbent material for heavy metal ion adsorption in aqueous solution, automobile exhaust purification, impurity removal of printing ink and gas separation; or / and as a supercapacitor electrode material or energy storage material.

Citation Information

Patent Citations

  • A kind of koh solid activated activated carbon preparation and molding method

    CN105293491B

  • Preparation and application of nitrogen-rich porous activated carbon adsorbent derived from microporous polymer

    CN112892477A

  • Preparation method of straw activated carbon, straw activated carbon and application

    CN113582174A